KOORDINASI DALAM PENERTIBAN BANGUNAN LIAR DI KECAMATAN TANJUNG PRIOK KOTA JAKARTA UTARA - Amanda Savira; Neneng Weti Isnawaty; Nina Karlina (Universitas Padjadjaran, 2023)
This research discussed the coordination of controlling illegal buildings in Tanjung Priok District, North Jakarta City. The policy regarding integrated control in Tanjung Priok District, North Jakarta City. The policy regarding integrated control in Tanjung Priok District, North Jakarta City has been stipulated in the Instruction of the Governor of DKI Jakarta Number 118 of 2016 concerning Integrated Control. The implementation of building control requires coordination between the parties involved so it can run smoothly, but in practice the coordination of building control in Tanjung Priok District, North Jakarta City hasn’t been implemented well, therefore the author is interested in conducting research related to this topic. The research method is a qualitative research method to explore and understand the coordination in controlling illegal buildings in Tanjung Priok District, North Jakarta City. The theory used as a reference (guidance) in this research is six effective coordination techniques by Chandra Bose (2012): clearly defined goals, line of authority and responsibilities, comprehensive programs and policies, cooperation, effective communication, and effective leadership and supervision. The result of this research is the coordination that has been carried out by the parties involved in controlling illegal buildings in Tanjung Priok District, North Jakarta City has been done properly in terms of clear objectives and clear division of tasks and authorities. However, other matters such as comprehensive programs and policies, cooperation, effective communication, and effective leadership and supervision have not been well implemented. Penelitian ini membahas tentang koordinasi dalam penertiban bangunan liar di Kecamatan Tanjung Priok Kota Jakarta Utara. Kebijakan mengenai penertiban terpadu di Kecamatan Tanjung Priok Kota Jakarta Utara ditetapkan dalam Instruksi Gubernur DKI Jakarta Nomor 118 Tahun 2016 Tentang Penertiban Terpadu. Pelaksanaan penertiban bangunan memperlukan koordinasi antara pihak-pihak yang terlibat agar dapat berjalan secara lancar, namun pada pelaksanaannya koordinasi penertiban bangunan di Kecamatan Tanjung Priok Kota Jakarta Utara belum berjalan dengan baik sehingga penulis tertarik untuk melakukan penelitian terkait hal tersebut. Metode penelitian yang digunakan oleh penulis adalah metode penelitian kualitatif untuk mengeksplorasi dan memahami tentang koordinasi dalam penertiban bangunan liar di Kecamatan Tanjung Priok, Kota Jakarta Utara. Teori yang dijadikan acuan (guidance) dalam penelitian ini yaitu teori Chandra Bose (2012) dengan menggunakan enam teknik koordinasi yang efektif yaitu tujuan yang jelas, garis wewenang dan tanggung jawab yang jelas, program dan kebijakan yang tepat dan berkelanjutan, kerjasama, komunikasi yang efektif, dan kepemimpinan dan pengawasan yang efektif. Hasil penelitian ini adalah koordinasi yang telah dilakukan oleh pihak-pihak yang terlibat dalam penertiban bangunan liar di Kecamatan Tanjung Priok Kota Jakarta Utara sudah baik dalam tujuan yang jelas serta pembagian tugas dan wewenang yang jelas. Namun, pada hal lainnya seperti program dan kebijakan yang tepat dan berkelanjutan, kerjasama, komunikasi yang efektif, dan kepemimpinan dan pengawasan yang efektif belum baik dalam pelaksanaannya.